Argumentieren im Widerstand - Markewitz, Friedrich (Sprache in Politik und Gesellschaft. Perspektiven und Zugänge)

Quantum Dot Molecule Devices with Optical Control of Charge Status and Electronic Control of Coupling - Bopp, Frederik; Rojas, Jonathan; Revenga, Natalia; Riedl, Hubert; Sbresny, Friedrich; Boos, Katarina; Simmet, Tobias; Ahmadi, Arash; Gershoni, David; Kasprzak, Jacek; Ludwig, Arne; Reitzenstein, Stephan; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Neue Polymerwerkstoffe - Der Schlüssel für die Industrialisierung - Klippstein, Sven Helge

Authentic Englishes.nrw – Developing and Using Interactive Teaching and Learning Materials on Varieties of English - Pape, Stefan; Fiege, Amanda Sophie; Mindt, Ilka (Selected Papers from the 2021 Conference of the German Association for the Study of English)

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. Eine explorative Studie - Caruso, Carina; Neuweg, Georg Hans; Wagner, Marlene; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung

Öffnung der Blackbox Hochschullehre durch kollaborative Autoethnografie - Autor:innengruppe , AEDiL (Ethnografie der Hochschule)

Kollaborative Autoethnographien digitaler Praktiken. Eine konzeptionelle, methodische und theoretische Einführung zu einem Lehr-Forschungsprojekt im ersten Corona-Semester - Steinhardt, Isabel (DNGPS Working Paper)
Keywords: Open Science; kollaborative Autoethnographie

MapOSR - A mapping review dataset of empirical studies on Open Science - Lasser, Jana; Schneider, Jürgen; Lösch, Thomas; Röwert, Ronny; Heck, Tamara; Bluemel, Clemens; Neufend, Maike; Steinhardt, Isabel; Skupien, Stefan (F1000Research)
<ns3:p>Research that investigates respective researchers’ engagement in Open Science varies widely in the topics addressed, methods employed, and disciplines investigated, which makes it difficult to integrate and compare its results. To investigate current outcomes of Open Science research, and to get a better understanding on well-researched topics and research gaps, we aimed at providing an openly accessible overview of empirical studies that focus on different aspects of Open Science in different scientific disciplines, academic groups and geographical regions. In this paper, we describe a data set of studies about Open Science practices retrieved following a PRISMA approach to compile a literature review. We included studies from the Scopus and Web of Science databases with keywords relating to Open Science between the years 2000 and 2020, as well as a snowball search for relevant articles. Studies that did not investigate any aspect of Open Science, or weren’t peer-reviewed were excluded, resulting in a total of 695 remaining studies.<ns3:italic> </ns3:italic>The data set was collaboratively annotated to ensure intercoder reliability of the coded data.</ns3:p>
Keywords: Open Science

Qualitative und quantitative Inhaltsanalyse: digital und automatisiert. Eine anwendungsorientierte Einführung mit empirischen Beispielen und Softwareanwendungen - Schneijderberg, Christian; Wieczorek, Oliver; Steinhardt, Isabel
Zur Inhaltsanalyse gibt es bereits diverse Methodenbücher. Warum sollten Sie also genau das vorliegende Methodenbuch „Qualitative und quantitative Inhaltsanalyse: digital und automatisiert “lesen? Erstens schließt dieses Buch eine Lücke, der wir in der Lehre und bei Methodenworkshops immer wieder begegnet sind. Diese Lücke besteht darin, dass selten eine Übersicht über und Gegenüberstellung verschiedener Methoden der qualitativen und quantitativen Inhaltsanalyse gegeben wird. Zudem haben bisherige Lehr-und Methodenbücher in den Sozialwissenschaften teil-und vollautomatisierte Verfahren der Textanalyse noch nicht aufgegriffen und diese mit bereits etablierten Verfahren qualitativer und quantitativer Inhaltsanalyse verknüpft. Zweitens bietet dieses Buch im ersten Teil eine systematische und anwendungsorientierte Einführung zu den Grundlagen inhaltsanalytischer empirischer Sozialforschung. Im zweiten Teil werden detaillierte Anleitungen von digital unterstützten qualitativen inhaltsanalytischen Auswertungstechniken gegeben. Den teil-und vollautomatisierten quantitativen inhaltsanalytischen Auswertungstechniken widmet sich der dritte Teil des Buches. Bei digital unterstützten Verfahren werden Sie durch Software bei Ihrer Analyse unterstützt, beispielsweise bei der digitalen Organisation Ihrer Daten und bei der digitalen Durchführung der Auswertung. Bei teilautomatisierten Verfahren der Inhaltsanalyse nehmen Ihnen Software und Tools Teile der Datenanalyse ab, wohingegen bei vollautomatisierten Verfahren der gesamte Auswertungsprozess und oftmals auch die Datenbeschaffung durch Programme und Tools durchgeführt wird.
Keywords: qualitative Inhaltsanalyse; quantitative Inhaltsanalyse

Evaluating Accents of English in ELT Textbooks Used at German Secondary Schools - Scheiwe, Lisa (Anglistik)

Correction to: Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey - Bühlmeier, Judith; Frölich, Stefanie; Ludwig, Christine; Knoll-Pientka, Nadja; Schmidt, Börge; Föcker, Manuel; Libuda, Lars (European Journal of Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Age at menarche relates to depression in adolescent girls: Comparing a clinical sample to the general pediatric population - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Kuhnert, Ronny; Cohrdes, Caroline; Peters, Triinu; Hebebrand, Johannes; et al. (Journal of Affective Disorders)
Keywords: Psychiatry and Mental health; Clinical Psychology

An explicit symplectic approach to solving the wave equation in moving media - Inguva, Venkatesh; Feldmann, Nadine; Claes, Leander; Koturbash, Taras; Hahn-Jose, Thomas; Koutcherov, Vladimir; Kenig, Eugeny (Engineering Reports)
An explicit approach using symplectic time integration in conjunction with traditional finite difference spatial derivatives to solve the wave equation in moving media is presented. A simple operator split of this second order wave equation into two coupled first order equations is performed, allowing these split equations to be solved symplectically. Orders of symplectic time integration ranging from first to fourth along with orders of spatial derivatives ranging from second to sixth are explored. The case of cylindrical acoustic spreading in air under a constant velocity in a 2D square structured domain is considered. The variation of the computed time-of-flight, frequency, and wave length are studied with varying grid resolution and the deviations from the analytical solutions are determined. It was found that symplectic time integration interferes with finite difference spatial derivatives higher than second order causing unexpected results. This is actually beneficial for unstructured finite volume tools like OpenFOAM where second order spatial operators are the state-of-the art. Cylindrical acoustic spreading is simulated on an unstructured 2D triangle mesh showing that symplectic time integration is not limited to the spatial discretization paradigm and overcomes the numerical diffusion arising with the in-built numerical methods which hinder wave propagation.

"Ein Steuerzahler!" Tax education in der frühen Bundesrepublik - Schönhärl, Korinna (Ökonomie und Moral im langen 20. Jahrhundert. Eine Anthologie)

Reconciliation in Resignation: The 2015 Greek Referendum on the Lenders’ Conditions - Schönhärl, Korinna (Journal of European Integration History)

Mehrsprachigkeit: Aspekte von Forschung und Messung - Gövert, Andre; Havkić, Amra; Settinieri, Julia (Handbuch Mehrsprachigkeit)

Long-Term Memory Recursive Least Squares Online Identification of Highly Utilized Permanent Magnet Synchronous Motors for Finite-Control-Set Model Predictive Control - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Untersuchung von Gefahrensituationen bei industriellen Absorption/Desorption-Prozessen mittels dynamischer Simulation - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y.

Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (Approximation and Online Algorithms)

Adjustment of AgCaLa Phases in a FeMn Matrix via LBM for Implants with Adapted Degradation - Krüger, Jan Tobias (crystals)

Atar-Gull o Una venganza africana de Lucio V. Mansilla: un drama del romanticismo transatlántico - Schlieper, Hendrik (El drama histórico en los romanticismos de España e lberoamérica. Procesos transnacionales de intercambio y renegociación de identidades. (Teoría y Práctica del Teatro, 29))

Knoten/Schreiben: Graffignys Lettres d’une Péruvienne und die transatlantische Schrift-Kultur-Debatte - Schlieper, Hendrik (Transatlantische Aufklärung. Erfahrungen von Identität und Alterität im 18. Jahrhundert)

The ‚Empire‘ Writes Back: Literarische Rekolonialisierungen im Frankreich des 18. Jahrhunderts (Prévost, Lesage, Fuzelier/Rameau) - Schlieper, Hendrik (200 Jahre Nationalphilologien. Von der Romantik zur Globalisierung)

Transatlantische Aufklärung. Einleitende Überlegungen - Schlieper, Hendrik; Roselli, Antonio (Transatlantische Aufklärung. Erfahrungen von Identität und Alterität im 18. Jahrhundert)

Im Namen des Vaters. Liebe, Sexualität und Familie in Carlo Goldonis "La locandiera" und Gotthold Ephraim Lessings "Emilia Galotti“ - Steigerwald, Jörn (Artes. Zeitschrift für Literatur und Künste der frühmodernen Welt, 1 / 1)

Transatlantische Aufklärung. Erfahrungen von Identität und Alterität im 18. Jahrhundert

Piezoelectric Ultrasonic Power Transducers - Hemsel, Tobias; Twiefel, Jens (Reference Module in Materials Science and Materials Engineering)
This article is dedicated to piezoelectric ultrasonic power transducers that differ to well known medical ultrasonic diagnostic apparatus or non destructive testing devices by the level of power in use; typically several tens of up to more than thousand watts are used in a multitude of different applications. After a short introduction including historical development, the first focus is on theoretical background of the operating principle, design and mechanical modeling. As piezoelectric elements transform electrical to mechanical energy and vice versa, equivalent circuit modeling is also described. After that, sample applications are delineated by the matter wherein ultrasound generates unique effects: incredible high pressure level as well in air as in water, micro-bubbles generating temperature peaks for very short time instances in fluids, acoustoplastic effect, enhancement of diffusion and recrystallization in solids, friction manipulation, incremental deformation and micro-cracking of surfaces, or even generation of macroscopic movements in motors. At the end, some future directions ranging from novel modeling approaches to advanced control and new materials are addressed.
Keywords: Equivalent circuit model; Langevin transducer; Lumped parameter model; Piezoelectric transducer; Ultrasonic processes; Ultrasound

Handlungsfelder für die KI-Einführung in der Arbeitswelt produzierender Unternehmen - Gabriel, Stefan; Aring, Theresa; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Tagungsband des 68. Frühjahrskongress der Gesellschaft für Arbeitswissenschaft)

Pattern based engineering of System of Systems - a systematic literature review - Anacker, Harald; Günther, Matthias; Wyrwich, Fabian; Dumitrescu, Roman (17th Annual System of Systems Engineering Conference (SOSE))

Identification of stakeholder-specific Systems Engineering competencies for industry - Anacker, Harald; Dumitrescu, Roman; Könemann, Ulf; Wilke, Daria (Proceedings of the 16th Annual IEEE International Systems Conference)

Lektürewege, Bildmaterialitäten und Medienreflexion in feuilletonistischen Stadtansichten der Weimarer Republik. - Öhlschläger, Claudia (Journale lesen. Lektüreabbruch-Anschlusslektüren. Reading Journals. Coherence and Interruption. (Reihe "Journalliteratur". Hrsg. von der Forschergruppe "Journalliteratur", Bd. 4))

Himmlische Klänge und Zaubergesänge in Torquato Tassos "Gerusalemme liberata“ - Steigerwald, Jörn (Literatur und Musik im Cinquecento: Zwischen septem artes liberales und Humanismus in Italien)

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))
In this work, methods will be evaluated to numerically calculate the passive electrical parameters of planar coils. These parameters can then be used to optimize inductive applications such as wireless power transmission. The focus here will be on inductive localization, which uses high-frequency magnetic fields and the resulting induced voltage to provide localization through the coupling parameter mutual inductance. To achieve localization with high accuracy and best possible operation (resonance, signal strength, etc.), the coil parameters need to be well known. For this reason, some numerical methods for the calculation of these quantities are presented and validated. In addition, the physical effects are thereby considered in more detail, allowing the localization procedure to be better optimized compared to simulative black-box methods. The goal should be a dedicated simulation platform for planar coils to be able to develop training data for neural networks and to test and optimize localization algorithms.
Keywords: Simulation Environment; Inductive Localization; Coil Parameters; Inductive Applications; Near-Field

Detection of Defects on Irregularly Structured Surfaces using Supervised and Semi-Supervised Learning Methods - Sander, Tom; Lange, Sven; Hilleringmann, Ulrich; Geneiß, Volker; Hedayat, Christian; Kuhn, Harald (2022 Smart Systems Integration (SSI))
In the manufacture of real wood products, defects can quickly occur during the production process. To quickly sort out these defects, a system is needed that finds damage in the irregularly structured surfaces of the product. The difficulty in this task is that each surface is visually different and no standard defects can be defined. Thus, damage detection using correlation does not work, so this paper will test different machine learning methods. To evaluate different machine learning methods, a data set is needed. For this reason, the available samples were recorded manually using a static fixed camera. Subsequently, the images were divided into sub-images, which resulted in a relatively small data set. Next, a convolutional neural network (CNN) was constructed to classify the images. However, this approach did not lead to a generalized solution, so the dataset was hashed using the a- and pHash. These hash values were then trained with a fully supervised system that will later serve as a reference model, in the semi-supervised learning procedures. To improve the supervised model and not have to label every data point, semi-supervised learning methods are used in the following. For this purpose, the CEAL method (wrapper method) is considered in the first and then the Π-Model (intrinsically semi-supervised).
Keywords: Machine Learning; CNN; Hashing; semi-supervised learning

Biopoethisches Wissen über Menschen und/als Klone: Der Entwurf einer hybriden Menschlichkeit in Kazuo Ishiguros "Never Let Me Go". - Hannebohm, Ronja (Wissenstransfer: Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung)

Development of an innovative separation unit for nitrogen recovery from agricultural waste - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny
Keywords: CFD; simulation; agricultural waste; multiphase

Projektmanagement und Vorgehensmodelle 2022. Virtuelle Zusammenarbeit und verlorene Kulturen? - Fazal-Baqaie, Masud; Linssen, Oliver; Volland, Alexander; Yigitbas, Enes; Engstler, Martin; Bertram, Martin; Kalenborn, Axel

Maßnahmen zur Reduzierung von plastischer Verformung an statischen Druckplatten von Lammellenbremsen infolge einseitig eingebrachter hoher Reibleistung - Schadomsky, Magnus; Blumenthal, Lars Martin; Zimmer, Detmar; Peter, Simon; Boros, Laszlo (Forschung im Ingenieurwesen)
Die thermisch verursachte, plastische Verformung an statischen Druckplatten von Lamellenbremsen kann das Betriebsverhalten von Bremsen nachhaltig stören und sollte daher vermieden werden. So kann die plastische Verformung der Druckplatte beispielsweise zu einer Verkleinerung des Luftspalts führen und ungewollte Veränderung der Reibverhältnisse verursachen. Während des Bremsvorgangs dehnen sich hoch erwärmte Bereiche nah der Reibfläche aus und werden von den Zonen geringerer Temperatur an ihrer Ausdehnung gehindert. Überschreiten die daraus resultierenden Spannungen die Dehngrenze des Materials, kommt es zu plastischer Verformung. Dieser Artikel erläutert den physikalischen Verformungsprozess detailliert und darauf aufbauend, welche Maßnahmen zu einer Verringerung der Verformung ergriffen werden können. Dazu werden im Rahmen theoretischer Vorüberlegungen drei Ansätze identifiziert, die sowohl die Geometrie als auch die Werkstoffe der Druckplatten betreffen. Radiale Schlitze sollen die Behinderung der thermischen Dehnung verhindern und dadurch Spannungen reduzieren; die Werkstoffauswahl auf Basis der Thermoschockempfindlichkeit reduziert die plastische Verformung. Anhand einer kombinierten Simulation der Thermik und der Mechanik einer Druckplatte wird der Effekt dieser Ansätze an vier Varianten der Druckplatte überprüft. Experimentelle Untersuchungen an realen Prototypen der Druckplattenvarianten bestätigen die Ergebnisse der Simulation und weisen die Wirksamkeit der vorgeschlagenen Maßnahmen zur Reduzierung der plastischen Verformung nach.
Keywords: General Engineering; Bremsen; Bremsscheiben; thermoplastische Verformung

Damage modeling in the numerical simulation of mechanical joining processes - Otroshi, Mortaza

Investigation of the three-dimensional stress state during loading of self-piercing riveted joints - Otroshi, Mortaza; Meschut, Gerson

Arzt-Patienten-Kommunikation und das Problem der Einverständniserklärung in Jeffrey Eugenides’ Roman Middlesex - Mildorf, Jarmila (Jahrbuch Literatur und Medizin)

Charge mentale et violence domestique: une approche des récits de femmes en termes de small stories - Mildorf, Jarmila (Récits de la charge mentale des femmes: small stories II)

Design Decisions in the Architecture Development of Advanced Systems: Towards traceable and sustainable Documentation and Communication - Pfeifer, Stefan; Akgül, Didem; Röbenack, Silke; Tihlarik, Amelie; Albert, Bruno; Anacker, Harald; Dumitrescu, Roman (DS 118: Proceedings of NordDesign 2022)

Design of an optimised value creation network for zero emission ferries - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Anacker, Harald; Dumitrescu, Roman (Proceedings of the IEEE)

Knowledge-based Interactive Configuration Tool for Industrial Augmented Reality Systems - Eckertz, Daniel; Anacker, Harald; Dumitrescu, Roman (Proceedings of the 5th International Conference on Information and Computer Technologies (ICICT))

Towards a Process Model to Enable Domain Experts to Become Citizen Data Scientists for Industrial Applications - Merkelbach, Silke; von Enzberg, Sebastian; Kuhn, Arno; Dumitrescu, Roman (Proceedings of the IEEE)

Systematics for the individual assessment of augmented reality potentials to support product validation - Eckertz, Daniel; Anacker, Harald; Dumitrescu, Roman (Proceedings of NordDesign 2022)

Implementation of Systems Engineering: A maturity-based approach - Wilke, Daria; Pfeifer, Stefan; Heitmann, Rebecca; Anacker, Harald; Dumitrescu, Roman; Franke, Volker (Proceedings of the IEEE ISSE)

Experimentelle Untersuchung des Ermüdungsverhaltens und Berechnung der Lebensdauer von Stahlklebverbindungen bei multiaxialer Belastung - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson

Fridolin-Duck Karotti. Mit einem kollaborativen Schreibtool gemeinsam Fantasiere beschreiben - Rezat, Sara; Scholle, Oliver; Bendner, Sarah (Praxis Deutsch 292)

Improved output gap estimates and forecasts using a local linear regression - Fritz, Marlon (International Economics)
Keywords: General Economics; Econometrics and Finance; General Business; Management and Accounting

Digital lesen und schreiben. Basisbeitrag - Rezat, Sara (Praxis Deutsch)

Second-harmonic generation in atomically thin 1T−TiSe2 and its possible origin from charge density wave transitions - Zhang, Ruiming; Ruan, Wei; Yu, Junyao; Gao, Libo; Berger, Helmuth; Forró, László; Watanabe, Kenji; Taniguchi, Takashi; Ranjbar, Ahmad; Belosludov, Rodion V.; Kühne, Thomas; Bahramy, Mohammad Saeed; et al. (Physical Review B)

Electronic Structures of Group III–V Element Haeckelite Compounds: A Novel Family of Semiconductors, Dirac Semimetals, and Topological Insulators - Khazaei, Mohammad; Ranjbar, Ahmad; Kang, Yoon‐Gu; Liang, Yunye; Khaledialidusti, Rasoul; Bae, Soungmin; Raebiger, Hannes; Wang, Vei; Han, Myung Joon; Mizoguchi, Hiroshi; Bahramy, Mohammad S.; Kühne, Thomas; et al. (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Real-Space Identification of Non-Noble Single Atomic Catalytic Sites within Metal-Coordinated Supramolecular Networks - Schulze Lammers, Bertram; López-Salas, Nieves; Stein Siena, Julya; Mirhosseini, Hossein; Yesilpinar, Damla; Heske, Julian Joachim; Kühne, Thomas; Fuchs, Harald; Antonietti, Markus; Mönig, Harry (ACS Nano)
Keywords: General Physics and Astronomy; General Engineering; General Materials Science

On the Role of Hydrogen Bond Strength and Charge Transfer of a Diels-Alder Reaction On-Water: Semiempirical and Free Energy Calculations. - Henao Aristizabal, Andres; Gohar, Yomna; Whilhelm, René; Kühne, Thomas
Accelerated chemistry at the interface with water has received increasing attention. The mechanisms behind the enhanced reactivity On-Water are not yet clear. In this work we use a Langevin scheme in the spirit of second generation Car-Parrinello to accelerate the second-order density functional Tight-Binding (DFTB2) method in order to investigate the free energy of two Diels-Alder reaction On-Water: the cycloaddition between cyclopentadiene and ethyl cinnamate or thionocinnamate. The only difference between the reactants is the substitution of a carbonyl oxygen for a thiocarbonyl sulfur, making possible the distinction between them as strong and weak hydrogen-bond acceptors. We find a different mechanism for the reaction during the transition states and uncover the role of hydrogen bonds along with the reaction path. Our results suggest that acceleration of Diels-Alder reactions do not arise from an increased number of hydrogen bonds at the transition state and charge transfer plays a significant role. However, the presence of water and hydrogen-bonds is determinant for the catalysis of these reactions.

CENT2: Improved charge equilibration via neural network technique - Khajehpasha, Ehsan Rahmatizad; Finkler, Jonas A.; Kühne, Thomas; Ghasemi, Alireza (Physical Review B)

Surface Passivation and Detrimental Heat-Induced Diffusion Effects in RbF-Treated Cu(In,Ga)Se2 Solar Cell Absorbers - Elizabeth, Amala; Sahoo, Sudhir K.; Phirke, Himanshu; Kodalle, Tim; Kühne, Thomas; Audinot, Jean-Nicolas; Wirtz, Tom; Redinger, Alex; Kaufmann, Christian A.; Mirhosseini, Hossein; Mönig, Harry (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Fingerprints Indicating Superior Properties of Internal Interfaces in Cu(In,Ga)Se 2 Thin‐Film Solar Cells - Raghuwanshi, Mohit; Chugh, Manjusha; Sozzi, Giovanna; Kanevce, Ana; Kühne, Thomas; Mirhosseini, Hossein; Wuerz, Roland; Cojocaru‐Mirédin, Oana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Do Lead Halide Hybrid Perovskites Have Hydrogen Bonds? - Ibaceta-Jaña, Josefa; Chugh, Manjusha; Novikov, Alexander S.; Mirhosseini, Hossein; Kühne, Thomas; Szyszka, Bernd; Wagner, Markus R.; Muydinov, Ruslan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian Joachim; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Time resolved THz-Raman spectroscopy reveals that cations and anions distinctly modify intermolecular interactions of water - Balos, Vasileios; Kaliannan, Naveen Kumar; Elgabarty, Hossam; Wolf, Martin; Kühne, Thomas; Sajadi, Mohsen

Who has the future in mind? Gender, time perspectives, and pro-environmental behaviour - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (Environmental Research Letters)
Abstract An individual’s relation to time may be an important driver of pro-environmental behaviour. We studied whether young individual’s gender and time-orientation are associated with pro-environmental behaviour. In a controlled laboratory environment with students in Germany, participants earned money by performing a real-effort task and were then offered the opportunity to invest their money into an environmental project that supports climate protection. Afterwards, we controlled for their time-orientation. In this consequential behavioural setting, we find that males who scored higher on future-negative orientation showed significantly more pro-environmental behaviour compared to females who scored higher on future-negative orientation and males who scored lower on future-negative orientation. Interestingly, our results are completely reversed when it comes to past-positive orientation. These findings have practical implications regarding the most appropriate way to address individuals in order to achieve more pro-environmental behaviour.
Keywords: Public Health; Environmental and Occupational Health; General Environmental Science; Renewable Energy; Sustainability and the Environment

Künstliche Intelligenz in der industriellen Arbeitswelt - Studie zum Status Quo in der Region OstWestfalenLippe - Papenkordt, Jörg; Gabriel, Stefan; Thommes, Kirsten; Dumitrescu, Roman
Im Rahmen dieser Studie wird der Status Quo des KI-Einsatzes in der industriellen Arbeitswelt in der Region OstWestfalenLippe erfasst und beschrieben. Dadurch wird eine Grundlage geschaffen, um eine zielführende Unterstützung der Gestaltung von durch Künstliche Intelligenz (KI) gestützter Arbeitsprozesse in Unternehmen zu ermöglichen, indem beispielsweise bedarfsbezogene Maßnahmen entwickelt und durchgeführt sowie weiterer Forschungsbedarf aufgezeigt wird. Die Befragung wurde im Jahr 2021 von dem Kompetenzzentrum Arbeitswelt.Plus sowie dem Spitzencluster it’s OWL initiiert. Dabei sind drei Zielgruppen – Unternehmensleitung, Personalabteilung (HR) sowie Arbeitnehmer*innen – adressiert worden. Insgesamt nahmen 317 Personen aus 89 verschiedenen Unternehmen bzw. Organisationen an der Befragung teil – zu 38 % Unternehmer*innen, zu 13 % Personaler*innen und zu 49 % Arbeitnehmer*innen. Die meisten der Teilnehmenden stammten aus der Elektroindustrie, dem Maschinenbau sowie dem Informations- und Kommunikationstechnologie (IKT)-Sektor. Die Befragungsergebnisse zeigen, dass sich die meisten Unternehmen in der Anfangsphase der KI-Nutzung befinden. Zwischen einzelnen Unternehmensbereichen und verschiedenen Branchen zeigen sich gewisse Unterschiede in der Nutzungsphase. Die Befragten stehen aktuell vor der Nutzung von vor allem teilautonomen KI-Systemen, die ausführende und analytische menschliche Tätigkeitenbeispielsweise durch Informationsbereitstellungen unterstützen. Wesentliche Ziele der KI-Nutzung sind die Effizienzsteigerung, Qualitätsverbesserung, Entscheidungsoptimierung sowie Unterstützung der Arbeitnehmer*innen. Allerdings werden in allen Unternehmen die fehlende Expertise sowie insgesamt die Komplexität des Themenfelds als Hinderungsgründe identifiziert. In allen Unternehmen und allen Unternehmensbereichen werden hohe Auswirkungen durch KI erwartet. Auf die Arbeitsgestaltung werden insgesamt eher positive Auswirkungen erwartet. Die Befragten schätzen die Bedeutung von KI, ihre Aufgeschlossenheit sowie ihr Vertrauen gegenüber KI als insgesamt hoch ein, ihr Verständnis von KI dagegen eher als gering. Tendenziell zeigt sich eine große Diskrepanz zwischen Selbst- und Fremdbild mit einer teils deutlich negativeren Wahrnehmung anderer. Die Befragten erwarten außerdem steigende Kompetenzanforderungen sowie einen hohen Weiterbildungsbedarf, insbesondere bezüglich des grundlegenden Verständnisses über KI. In den wenigsten Unternehmen existiert jedoch ein gezieltes Weiterbildungsangebot. Die Erkenntnisse aus der Befragung fließen im Rahmen des Kompetenzzentrums Arbeitswelt.Plus in die gezielte Gestaltung und Einführung KI-gestützter Arbeitsformen sowie bedarfsgerechter Unterstützungsangebote ein. Die hohe Komplexität der KI-Einführung sowie die sowohl technischen als auch mitarbeiterbezogenen Herausforderungen verdeutlichen den Bedarf für eine soziotechnische Perspektive und ein systematisches Vorgehen bei der Gestaltung dieses vielschichtigen Themenfelds.

Künstliche Intelligenz im Engineering - Kharatyan, Aschot; Humpert, Lynn; Anacker, Harald; Dumitrescu, Roman; Wäschle, Moritz; Albers, Albert; Horstmeyer, Sarah (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Künstliche Intelligenz bietet großes Potenzial im Engineering. Der Einsatz gestattet insbesondere für Wissensarbeiter eine effiziente Arbeitsteilung, in der beispielsweise fehleranfällige und repetitive Aktivitäten unterstützt werden. Eine erfolgreiche Einführung bedarf einer vorangehenden Analyse von nutzenstiftenden Einsatzpotenzialen, bei der alle Anwendenden frühzeitig einbezogen werden. Der folgende Beitrag verdeutlicht dieses Vorgehen anhand eines realen Beispiels im Sondermaschinenbau.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Planning the Analysis of Use Phase Data in Product Planning - Meyer, Maurice; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The ongoing digitalization of products offers product managers new potentials to plan future product generations based on data from the use phase instead of assumptions. However, product managers often face difficulties in identifying promising opportunities for analyzing use phase data. In this paper, we propose a method for planning the analysis of use phase data in product planning. It leads product managers from the identification of promising investigation needs to the derivation of specific use cases. The application of the method is shown using the example of a manufacturing company.

How can Data Analytics Results be Exploited in the Early Phase of Product Development? 13 Design Principles for Data-Driven Product Planning - Meyer, Maurice; Fichtler, Timm; Koldewey, Christian; Dumitrescu, Roman (AMCIS 2022 Proceedings)
The megatrend digitalization turns mechatronic products into continuous collectors and generators of use phase data. By analyzing this data, manufacturers can uncover valuable insights about the products and the users. Especially in product planning, these insights could be used to plan promising future product generations. The systematic exploitation of data analytics results, however, represents a serious challenge, as research on the topic is still scarce. In this paper, we present 13 design principles for exploiting data analytics results in product planning. The results are based on a systematic literature review and a workshop with a research consortium. The evaluation of the design principles is demonstrated with a real case of a manufacturing company. The identified design principles represent a first contribution to a still scarcely explored research field.

17 Use Cases for Analyzing Use Phase Data in Product Planning of Manufacturing Companies - Meyer, Maurice; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Model-based Analysis and Specification of Functional Requirements and Tests for Complex Automotive Systems - Wiecher, Carsten; Mandel, Constantin; Günther, Matthias; Fischbach, Jannik; Greenyer, Joel; Greinert, Matthias; Wolff, Carsten; Dumitrescu, Roman; Mendez, Daniel; Albers, Albert (arXiv preprint)

Evaluation of Industry 4.0 Applications in Production - Joppen, Robert; Kühn, Arno; Förster, Magdalena; Dumitrescu, Roman (Journal of the Knowledge Economy)
Abstract Industry 4.0 promises many potentials in production. Examples are a data-driven optimization of production processes of individual machines, driverless transport systems, and assistance systems. Nevertheless, companies are still hesitant to invest in Industry 4.0 applications. Studies show that one of the main reasons for that is the unclear economic benefit. In this work, we present a systematic approach for the evaluation of Industry 4.0 applications in production. The main goal of the systematic is to create transparency over the evaluation process of an investment in an Industry 4.0 application in production. The evaluation of a concrete technical solution in an existing production system is supported. As a theoretical foundation, a characterization of investments in Industry 4.0 applications is given. From that, a procedure model is derived. It puts the activities to be carried out, the tools to be used and results in a temporal context. The application of the systematic is shown on the basis of an application example.
Keywords: Economics and Econometrics

Collaborative Modeling of Use Case & Damage Scenarios in Online Workshops Using a 3D Environment - Japs, Sergej; Schmidt, Sebastian; Kargl, Frank; Kaiser, Lydia; Kharatyan, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of technical systems requires close cooperation of stakeholders from different disciplines. This collaboration takes place in workshops. Driven by digitalization and by the current pandemic such workshops take place primarily online. Suitable collaboration tools and methods are crucial to success. At the beginning of such workshops, use and damage scenarios are identified. In this paper, we presented a method and tool for identifying and modeling use and damage scenarios, which we evaluated in 14 online workshops with a total of 118 participants over a period of almost 3 years.

Why make it hard? - Usage of aggregated statistical data for risk assessment of damage scenarios in the context of ISO/SAE 21434 - Japs, Sergej; Kargl, Frank; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Efficient method for determining substrate parameters of additive manufactured spatial circuit carriers - Mager, Thomas; Jürgenhake, Christoph; Dumitrescu, Roman (2022 14th German Microwave Conference (GeMiC))

Use Case Driven Digital Twin Generation - Gollner, Denis; Klausmann, Tobias; Rasor, Rik; Dumitrescu, Roman (2022 IEEE 5th International Conference on Industrial Cyber-Physical Systems (ICPS))

Requirements analysis for an intelligent workforce planning system: a socio-technical approach to design AI-based systems - Gabriel, Stefan; Bentler, Dominik; Grote, Eva-Maria; Junker, Caroline; Wendischhoff, David Meyer zu; Bansmann, Michael; Latos, Benedikt; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Cross-industry methods for strategic planning of the digital transformation of small and medium sized enterprises - Förster, Magdalena; Kürpick, Christian; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Security- and Safety-Driven Functional Architecture Development Exemplified by Automotive Systems Engineering - Kharatyan, Aschot; Günther, Matthias; Anacker, Harald; Japs, Sergej; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Method for direct end customer integration into the agile product development - Humpert, Lynn; Röhm, Benjamin; Anacker, Harald; Dumitrescu, Roman; Anderl, Reiner (Procedia CIRP)
Keywords: General Medicine

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, C. R.; Böhnke, M.; Bobbert, M.; Meschut, G. (The Minerals, Metals & Materials Series)

Verhandlungen sexueller und kultureller Fremd- und Selbstbestimmungen in Kristina Aamand’s interkulturellem Adoleszenzroman „Wenn Worte meine Waffe wären“ - Zierau, Cornelia; Kofer, Martina (Interkulturelles Lernen mit Kinder- und Jugendliteratur (in Vorbereitung))

Wertorientierung und Werteverhandlungen in Emine Sevgi Özdamars Roman „Das Leben ist eine Karawanserei“ - Zierau, Cornelia (Türkisch-deutsche Studien Jahrbuch 2020: Wertorientierungen)

Türkisch-deutsche Studien Jahrbuch 2020: Wertorientierungen

Increasing Firm Performance through Industry 4.0—A Method to Define and Reach Meaningful Goals - Koldewey, Christian; Hobscheidt, Daniela; Pierenkemper, Christoph; Kühn, Arno; Dumitrescu, Roman (Sci)

Collaborative Modeling of Interoperable Digital Twins in a SoS Context - Göllner, Denis; Rasor, Rik; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Potentials and challenges of analyzing use phase data in product planning of manufacturing companies - Meyer, Maurice; Fichtler, Timm; Koldewey, Christian; Dumitrescu, Roman (Artificial Intelligence for Engineering Design, Analysis and Manufacturing)
The successful planning of future product generations requires reliable insights into the actual products’ problems and potentials for improvement. A valuable source for these insights is the product use phase. In practice, product planners are often forced to work with assumptions and speculations as insights from the use phase are insufficiently identified and documented. A new opportunity to address this problem arises from the ongoing digitalization that enables products to generate and collect data during their utilization. Analyzing these data could enable their manufacturers to generate and exploit insights concerning product performance and user behavior, revealing problems and potentials for improvement. However, research on analyzing use phase data in product planning of manufacturing companies is scarce. Therefore, we conducted an exploratory interview study with decision-makers of eight manufacturing companies. The result of this paper is a detailed description of the potentials and challenges that the interviewees associated with analyzing use phase data in product planning. The potentials explain the intended purpose and generic application examples. The challenges concern the products, the data, the customers, the implementation, and the employees. By gathering the potentials and challenges through expert interviews, our study structures the topic from the perspective of the potential users and shows the needs for future research.
Keywords: Artificial Intelligence; Industrial and Manufacturing Engineering

EngOps – Ein Leitbild für das agile Zusammenwirken von Engineering und Operations - Anacker, Harald; Dumitrescu, Roman; Michels, Nico; Rasor, Rik (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Um global erfolgreich zu bleiben, wird es bald nicht mehr ausreichen, Kriterien wie ein gutes Produktdesign zu erfüllen. Stattdessen muss der Kundennutzen kontinuierlich über den Produktlebenszyklus hinaus gesteigert werden. Tech-Konzerne verzeichnen bereits Erfolge und verkörpern den Wandel schon heute. Vor diesem Hintergrund ist ein neues Leitbild in der Entwicklung und dem Betrieb von zukünftigen, technischen Systemen erforderlich. EngOps soll diesen Bedarf decken und steht für die agile Kollaboration zwischen Engineering und Operations. Alle Teile des Unternehmens sollen ständig miteinander kooperieren, um so beispielsweise wandelbare Produkte auch nach dem Verkauf entwickeln zu können.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

An In-depth Study of Java Deserialization Remote-Code Execution Exploits and Vulnerabilities - Sayar, Imen; Bartel, Alexandre; Bodden, Eric; Le Traon, Yves (ACM Transactions on Software Engineering and Methodology)
Nowadays, an increasing number of applications uses deserialization. This technique, based on rebuilding the instance of objects from serialized byte streams, can be dangerous since it can open the application to attacks such as remote code execution (RCE) if the data to deserialize is originating from an untrusted source. Deserialization vulnerabilities are so critical that they are in OWASP’s list of top 10 security risks for web applications. This is mainly caused by faults in the development process of applications and by flaws in their dependencies, i.e., flaws in the libraries used by these applications. No previous work has studied deserialization attacks in-depth: How are they performed? How are weaknesses introduced and patched? And for how long are vulnerabilities present in the codebase? To yield a deeper understanding of this important kind of vulnerability, we perform two main analyses: one on attack gadgets, i.e., exploitable pieces of code, present in Java libraries, and one on vulnerabilities present in Java applications. For the first analysis, we conduct an exploratory large-scale study by running 256 515 experiments in which we vary the versions of libraries for each of the 19 publicly available exploits. Such attacks rely on a combination of gadgets present in one or multiple Java libraries. A gadget is a method which is using objects or fields that can be attacker-controlled. Our goal is to precisely identify library versions containing gadgets and to understand how gadgets have been introduced and how they have been patched. We observe that the modification of one innocent-looking detail in a class – such as making it public – can already introduce a gadget. Furthermore, we noticed that among the studied libraries, 37.5% are not patched, leaving gadgets available for future attacks. For the second analysis, we manually analyze 104 deserialization vulnerabilities CVEs to understand how vulnerabilities are introduced and patched in real-life Java applications. Results indicate that the vulnerabilities are not always completely patched or that a workaround solution is proposed. With a workaround solution, applications are still vulnerable since the code itself is unchanged.
Keywords: Software

Fluently specifying taint-flow queries with fluentTQL - Piskachev, Goran; Späth, Johannes; Budde, Ingo; Bodden, Eric (Empirical Software Engineering)

To what extent can we analyze Kotlin programs using existing Java taint analysis tools? - Krishnamurthy, Ranjith; Piskachev, Goran; Bodden, Eric

How far are German companies in improving security through static program analysis tools? - Piskachev, Goran; Dziwok, Stefan; Koch, Thorsten; Merschjohann, Sven; Bodden, Eric

On the Treatment of Optimization Problems with L1 Penalty Terms via Multiobjective Continuation - Bieker, Katharina; Gebken, Bennet; Peitz, Sebastian (IEEE Transactions on Pattern Analysis and Machine Intelligence)
We present a novel algorithm that allows us to gain detailed insight into the effects of sparsity in linear and nonlinear optimization, which is of great importance in many scientific areas such as image and signal processing, medical imaging, compressed sensing, and machine learning (e.g., for the training of neural networks). Sparsity is an important feature to ensure robustness against noisy data, but also to find models that are interpretable and easy to analyze due to the small number of relevant terms. It is common practice to enforce sparsity by adding the ℓ1-norm as a weighted penalty term. In order to gain a better understanding and to allow for an informed model selection, we directly solve the corresponding multiobjective optimization problem (MOP) that arises when we minimize the main objective and the ℓ1-norm simultaneously. As this MOP is in general non-convex for nonlinear objectives, the weighting method will fail to provide all optimal compromises. To avoid this issue, we present a continuation method which is specifically tailored to MOPs with two objective functions one of which is the ℓ1-norm. Our method can be seen as a generalization of well-known homotopy methods for linear regression problems to the nonlinear case. Several numerical examples - including neural network training - demonstrate our theoretical findings and the additional insight that can be gained by this multiobjective approach.

An update for taxonomy designers: Methodological guidance from information systems research - Kundisch, Dennis; Muntermann, J.; Oberländer, A. M.; Rau, D.; Röglinger, M.; Schoormann, T.; Szopinski, Daniel (Business & Information Systems Engineering)

Durchdrungenheit. Texte und Gespräche. - Eke, Norbert; Zaimoglu , Feridun

Investigation and Improvement of Processing Parameters of a Copper-Filled Polymer Filament in Fused Filament Fabrication as a Basis for the Fabrication of Low-Porosity Metal Parts - Moritzer, Elmar; Elsner, Christian Lennart (Macromolecular Symposia)

Development of a Procedure for the Assessment of Material Potentials under Consideration of the Weld Seam Quality for Multi-Material Applications in the FDM Process - Moritzer, Elmar; Wächter, Julian (Macromolecular Symposia)

Deformationsarme Fügeverbindungen mittels prozessoptimiertem Schneidclinchen - Han, Daxin
Lightweight materials such as aluminium and ultra-high-strength steel are increasingly being used in modern material mixed design in car body construction. As a fixing method for hybrid joining with structural adhesive, clinching has the advantage over other mechanical joining technologies that different materials can be joined without an auxiliary joining part and pre-hole. Due to the large degree of deformation in the joining partners, strong in-plane and out-of-plane material flows occur during the setting process, which can lead to plastic deformation. The aim of this work is the further development of shear-clinching for low-deformation of aluminium-steel joints. To gain a basic understanding of the joint deformation, the deformation of the joint partners during the setting process is identified step by step. Based on the knowledge gained, the deformation-related influencing factors are investigated experimentally. Thus, optimisation approaches as well as suggested handling methods for the production of a low-deformation shear-clinching joint are derived. For the realisation of the common narrow flange, which is to be characterised as deformation-sensitive due to a small edge distance, a numerically supported tool modification is carried out and subsequently experimentally validated.

Differentiation of an SBFE model in the context of material parameter determination - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Birk, Carolin; Henning, Bernd

Theater und Krise. Paradigmen der Störung in Dramentexten und Bühnenkonzepten nach 2000, (= Drama zwischen Text und Bühne 1)

Judgment or Choice? An Experimental Comparison of Evaluation Approaches for External Crowdvoting - Laux, Florian; Kundisch, Dennis